Mapping research over 50-years on odontogenic keratocyst: Global data and bibliometric profile analysis (Research, Society and Development, 2023)
Oral and maxillofacial pathology is a traditional matter of study. The objective of this research is to perform a bibliometric analysis of odontogenic keratocyst over a length of fifth years. A bibliographic search (retrospective study) in line with the STROBE guidelines and the concepts of the Leiden Manifesto was performed on the Web of Science using the term “odontogenic keratocyst”. A citation analysis as so authorship, and year of publication were performed. A graphical representation of the keywords was created with VOSviewer. These steps are essential to create this list and relate it to all published articles on the subject. A ranking was created in which the top 51 most frequently referred articles. Variables had been discussed individually. The USA leads the number of publications, followed by Brazil and England. A massive variety of publications refer to recurrence after treatment and its association with tumoral antigen expression. The importance of choosing suitable keywords was discussed. The bibliometric indicators validate records to evaluate the overall performance of studies productiveness and the quality of research output. This work provides a treasured reference for maxillofacial surgeons, oral pathologists, academics and researchers.